2009
DOI: 10.1007/s00415-009-5344-7
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction following herpetic meningoencephalitis

Abstract: Herpetic meningoencephalitis (HME) is a rare but often lethal herpes simplex infection. Patients who survive generally retain neurological deficits. The literature consists mostly of autopsy reports and consistently shows the peripheral and central olfactory pathways to be severely damaged. Little information is available on degree and recovery of olfactory impairment following HME. In this retrospective case series, three patients (two women, one man) who had survived HME were tested with standardized olfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Permanent anosmia has been described in patients who recovered from HSE ( Landis et al 2010 ). Post-HSE anosmia often presents with other neurological sequelae, including epilepsy, amnesia, and cognitive deficits.…”
Section: Possible Mechanisms Of Anosmia In Sars-cov-2 Patientsmentioning
confidence: 99%
“…Permanent anosmia has been described in patients who recovered from HSE ( Landis et al 2010 ). Post-HSE anosmia often presents with other neurological sequelae, including epilepsy, amnesia, and cognitive deficits.…”
Section: Possible Mechanisms Of Anosmia In Sars-cov-2 Patientsmentioning
confidence: 99%
“…Warner et al first suggested olfactory impairments in patients with AD, employing a standardized smell identification test [ 23 ]. However, the lowered ability to distinguish between or recognize different odors is not exclusive for AD, as olfactory dysfunctions have also been detected in Parkinson's disease [ 24 , 25 ], multiple sclerosis [ 26 , 27 ], viral infections [ 28 , 29 ], lesions in the brain [ 30 ], and aging [ 31 ]. Thus, while there is a need for an olfactory test for AD, it should also be specific.…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory dysfunction is present in patients who survive herpes encephalitis [113]. In the early studies of Mann et al [114], HSV1 antigens were detected in the olfactory tract.…”
Section: Olfactory Dysfunction In Admentioning
confidence: 99%